Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE), 2017 2017
DOI: 10.23919/date.2017.7927039
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting computation skip to reduce energy consumption by approximate computing, an HEVC encoder case study

Abstract: Approximate computing paradigm provides methods to optimize algorithms with considering both computational accuracy and complexity. This paradigm can be exploited at different levels of abstraction, from technological to application levels. Approximate computing at algorithm level aims at reducing computational complexity by approximating or skipping block functions of the computation. Numerous applications in the signal and image processing domain integrate algorithms based on discrete optimization techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To validate this claim, we consider strict power budgets of 5W and 15W in Sec. VII, which is common for edge devices 8 . For both these power budgets, the accurate setting (S0) results in LKAS failure due to long sampling period (see Fig.…”
Section: A Results Summary and Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate this claim, we consider strict power budgets of 5W and 15W in Sec. VII, which is common for edge devices 8 . For both these power budgets, the accurate setting (S0) results in LKAS failure due to long sampling period (see Fig.…”
Section: A Results Summary and Insightsmentioning
confidence: 99%
“…Compute-centric approximations: Compute-centric efforts are focused on reducing the compute workload across algorithm, architecture and circuit-levels. Commonly used algorithmic approximations are computation skipping [8], precision scaling [9] and replacing error-resilient computeintensive functions with neural networks [10]. A similar learning approach to design ISPs for new camera systems is proposed in [11].…”
Section: Related Workmentioning
confidence: 99%
“…Another case study, showing advantages of approximate computing in the domain of biometric security systems, targeting an iris scanning application is demonstrated in [13]. The impact of approximate computing on a high-efficiency video coding (HEVC) encoder is explored in [14] leading to considerable energy benefits that can enable the use of such encoders in ultra-low power applications such as in the Internet of Things (IoT) domain. Approximation of compute-intensive nonlinear model predictive control (NMPC) algorithms for deployment in low-power embedded systems is shown in [15].…”
Section: Related Workmentioning
confidence: 99%
“…Justusson et al[5] discussed the use of estimated registering in equipment based PC vision. Receiving the ideas of versatile pressure and inexact quantization, C. Chen et al[6] proposed a picture sensor structure for PC vision undertakings that altogether moves the pixel organize scheme, sub sampled picture information that accomplish a significant decrease in vitality while keeping the classification exactness of regular DNN datasets, for example, the CIFAR-10, inside satisfactory levels. J. Baili et al[8] identified that assumed figuring can be used in spaces other than AI or picture preparing and showed a start to finish contextual investigation on the space of biometric security frameworks focusing on an iris checking application.…”
mentioning
confidence: 99%